2020
DOI: 10.1111/jfbc.13181
|View full text |Cite
|
Sign up to set email alerts
|

Citrus aurantium L. bloom essential oil nanoemulsion: Synthesis, characterization, cytotoxicity, and its potential health impacts on mice

Abstract: This research was performed to synthesize the Citrus aurantium L. bloom essential oil nanoemulsion (CABE‐NE) and investigate its cytotoxic and apoptotic impacts on human lung (A549 cells), and further, the effects of CABE‐NE on mice health parameters was determined. The obtained results demonstrated that C. aurantium bloom contained 1.2 ± 0.16% of essential oil with linalyl acetate, limonene, and α‐terpineol as major compounds. The CABE‐NE possessed particle size of 76.9 ± 6.11 nm, PDI of 0.19, and zeta potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 62 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…For instance, a study confirmed that by loading limonene into ChiNPs with a particle size of 339.5 nm, its antioxidant became more potent by improving its solubility [ 40 ]. CAEO nanoemulsion showed cytotoxicity against A549 cells with the IC 50 value of 152 μg/mL [ 41 ]. Besides, isolated nanovesicles from C. lemon have been shown an inhibitory effect in a time-dependent manner on cancer cell proliferation in different tumor cell lines by inducing apoptotic cell processes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study confirmed that by loading limonene into ChiNPs with a particle size of 339.5 nm, its antioxidant became more potent by improving its solubility [ 40 ]. CAEO nanoemulsion showed cytotoxicity against A549 cells with the IC 50 value of 152 μg/mL [ 41 ]. Besides, isolated nanovesicles from C. lemon have been shown an inhibitory effect in a time-dependent manner on cancer cell proliferation in different tumor cell lines by inducing apoptotic cell processes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of essential oil to non-ionic surfactant was 1:3 (v/v). Then, the ultrasonication was applied to homogenate emulsions at 20kHz ultrasonic frequency and 750 watts for 30 minutes sonication [29].…”
Section: The Preparation Of Sabe-nementioning
confidence: 99%
“…The last medium passed 10 minutes stirring. In the end, the absorbance at 570 nm was read for all samples utilizing plate reader spectrophotometer [29]. The cells viability was calculated by the following equation: Cell viability (%) = (OD sample/OD control) × 100.…”
Section: Mtt Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoemulsion of Citrus aurantium L. ( C. aurantium , bitter orange) bloom EO, containing linalyl acetate, limonene, and α-terpineol as major compounds, affected lung cancer progression. This nanoemulsion was able to onset apoptosis in A549 cells, without inducing a remarkable histopathological alteration of liver and kidney in mice, while it exhibited enhancement in the jejunum morpho-structural architecture and hepatic antioxidant redox potential [ 110 ].…”
Section: Nanoformulations Involving Vegetable Oil-based Nutraceutimentioning
confidence: 99%